Reviewing and Updating BDS Curriculum Stakeholders Views - Talukder, Md Humayun Kabir; Chowdhury, Fatima Parveen; Kashem, Abul; Azad, SM Salahuddin Al; Hossain, Zakir; Abeer, Chowdhury Nasrath Munir; Islam, Tania (City Dental College Journal, 2013)
This descriptive type of cross-sectional study was conducted to identify the need for reviewing and updating the existing Bachelor of Dental Surgery (BDS) curriculum. The study was conducted in different government and nongovernment dental colleges of Bangladesh in January to March 2013. Self-administered structured questionnaire was used to collect data. Teachers of different levels, intern doctors and final year BDS students were included in the study. Convenient sampling was done and the sample size was 63. A total number of three focus group discussions were conducted including 65 teachers as participants. Study revealed that the course duration should be five years instead of 4 years. Organizational structures of 5 years BDS course would be as MBBS course consisting of four phases. Duration of the 1st BDS curriculum would be 1 & ½ years, 2nd phase 1 year, 3rd phase 1 year and the 4th phase would be 1 & ½ years duration. There would be four professional university examinations for four phases within the specific duration. Redistribution and renaming of the few subjects in total course were also suggested. DOI: http://dx.doi.org/10.3329/cdcj.v10i2.16313 City Dent. Coll. J Volume-10, Number-2, July-2013